Upaya penanganan gangguan bersihan jalan nafas pada pasien tuberculosis di rsud dr. Soehadi prijonegoro - Wibowo, Arif; , Ns. Arief W. Jadmiko, S.Kep., M.Kep (2016)
Background: According to WHO, in 2010, one of the causes of death in the world is tuberculosis, in the fourth ranks. Tuberculosis is a chronic disease which is caused by Mycobacterium tuberculosis bacterium, a typical of microbe bacteria with a rod-shaped and length of about 1-4 mm with a thickness from 0.3 to 0.6 mm. The microbe structured is fat and capable to take longer with a variety of physical disorders, chemicals and acids. Common problem of disorder arises in the pulmonary tuberculosis (TB) is airway clearance disorder, nutritional imbalance less than the needs, intolerance activity, less needs. One of the problems that need special management is the disorder of airway clearance. Metods: In this research, the researcher applied a case study method which was done by using the nursing procces approach including interviews, observation, and documentation taken from a medical record. Objective: Through this research, the researcher will be able to understand the nursing management of patients with Tuberculosis airway clearance disorder at Melati inpatient room of Sragen Regional Hospital. Results: Based on the result of the research, the researcher concluded that the right nursing diagnoses for Mrs. P is airway clearance disorders associated with the accumulation of secretions. Having done 3x24 hours nursing management with the implementation such as monitoring respiration, performing chest physiotherapy, teaching for effenctive coughing, collaborating with the medical section in the delivery of oxygen. Through the nursing management, the problem of airway clearance disorder can be resolved. Further interventions associated with airway clearance disorder, effective coughing is necesarry to help to remove the secretions for smooth breathing. Conclusion: Nursing problem of airway clearance disorder has been resolved and therefore, it is important to do further action in order to achieve the outcomes. It is also important for cooperating with other medical teams, families and patients to achieve well nursing management. The implementation of an effective coughing is able to clear the airway and remove the excess sputum production.